In Vivo Analgetic Activity Test of Malacca Stem Bark Extract (Phyllanthus emblica L.) by Acetic Acid Induction Method - Novisma, Mutia; Saputri, Legis Ocktaviana; Hanifa, Nisa Isneni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The use of analgesics for pain management has limitations related to side effects, effectiveness, and dependence that are often caused. The malacca plant (Phyllanthus emblica L.) has been used empirically on Sumbawa Island to treat throat pain. This study aims to test the analgesic activity of malacca stem bark extract (EKBM) in vivo with acetic acid induction method. Mice were randomly divided into 5 groups including negative control (K-) CMC Na 1%, positive control (K+) ibuprofen 52 mg/KgBB mice, and various doses EKBM1, EKBM2, and EKBM3 consecutively 250, 500, 750 mg/KgBB mice orally. Analgesic activity was assessed based on the number of writhes, % analgesic protection, and % analgesic effectiveness. Phytochemical screening results showed that EKBM contains flavonoids, saponins, steroids, and tannins. The mean number of writhes in groups K (-), K (+), EKBM1, EKBM2, and EKBM3 were 105,60; 75,60; 60,60; 59,40; and 40,20, respectively. The results of one way ANOVA on the number of writhes showed that there were significant differences between all groups (p < 0.05). Furthermore, LSD test was conducted which showed that there were significant differences (p < 0.05) in all EKBM groups compared to K (+) and K (-). There was no significant difference between EKBM1 and EKBM2 groups (p > 0.05). The % analgesic protection values obtained by EKBM1, EKBM2, and EKBM3 were 42,61%; 43,74%; and 61,93%, respectively, while the % analgesic effectiveness values were 150%; 154%; and 218%. Based on the analgesic activity test, EKBM at three dose variations showed analgesic activity.